Tišina - Bjelica, Maja (Monitor ISH, 2023)
The paper looks at the culture of silence as key to becoming and to the sharing of life. Silence, easily imaginable and understandable, on the one hand, and unattainable, yet still frightening, on the other, is only conceivable in this simultaneity or ambiguity, since in its many manifestations it is never fully representative of itself. This essay focuses on silence as an atmosphere, a state that fosters the emergence of intersubjective relations and as such becomes an intersubjective gesture. Offering silence allows subjects the space for their own expression and thereby a way of being/living proper to themselves. In this way, silence also provides the possibility of communication, deeper attention and more accurate understanding, even though not necessarily by means of language. In fact, silence can be seen as an availability, an open space that a fellow human being can be offered and welcomed into. In this way, it allows for the arrival of the unexpected, which is another essential element of hospitality. These aspects are first tackled within the spheres of acoustics and literature, and subsequently ethics, devoting attention to the insights of philosophers such as Emmanuel Levinas, Jacques Derrida, and Luce Irigaray.
Keywords: cohabitation; ethics; Etika; Filozofija; gostoljubnost; Govor; govor in tišina; hospitality; intersubjective space; prostor intersubjektivnosti; silence; sobivanje; speech and silence; Tišina; transhumanism